Pembentukan Karakter Anak Melalui Pembelajaran Daring Dalam Bidang Akidah Akhlaq Pada Masa Pandemi Covid 19 di MA Balongrejo Sumobito Jombang - A. Syafi' AS.; Abdul Natsir (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2023)
This study aims to examine strategies for building children's character through online learning in the field of moral creed during the Covid-19 pandemic at MA Balongrejo Sumobito Jombang. In this study, the authors used a qualitative descriptive approach with data collection techniques through interviews/interviews with moral creed teachers and online with children via WhatsApp complete with documentation. While the data analysis technique uses descriptive qualitative with data reduction steps, data presentation and conclusion/verification. The results of the study show that during the PSBB period during the Covid 19 pandemic, MA Balongrejo Sumobito Jombang students are still expected to be able to take part in online learning using HP technology with adequate applications, but if there are students who cannot take part in online learning, educators must provide lessons with Offline (Home Visit). This was done with the hope that they would also be able to meet the guardians of the students, and also be able to help shape children's character in the field of morals such as speaking politely, being religious and making parents proud of their good ethics. Keywords : Character Building, Aqidah Akhlak, Online Learning